(untitled) (Orfeu, 2018)
With an emphasis on her artistic work, the present article recovers biographical traces of Paquita Baylina, a musician from Rio Grande do Sul who had a significant role in Porto Alegre’s cultural scene between the years 1910-1923. An unknown figure in the present day, Paquita had lessons with the blind teacher Levino Albano da Conceição and won a performance competition in 1914, thus acquiring prestige and recognition in a predominantly male environment. However, her musical activities were suddenly interrupted by her wedding in 1923, a factor which caused her double role to remain obscured for decades: as the probable first female guitarist to perform solo repertoire in the city’s main musical venues (including performances at the São Pedro theatre), and as a forerunner of the simultaneous practice of singing with guitar accompaniment. Upon gathering almost 100 previously unknown sources in magazines and newspapers, mostly from Rio Grande do Sul, but also from Rio de Janeiro and Bahia, it was possible to reconstruct the most important aspects of her musical career, bringing to light a woman that was considered by the critics of her time as a “skilled”, “intelligent” and “distinct virtuosa”.